Diamagnetically levitating three phase motor with optical feedback control - Shrey Khanna (2018)
This article describes a feasibility study of creating a low friction, low maintenance power delivering motor using a diamagnetically stabilized levitating rotor. The planar rotor described in this article uses a triangular configuration of magnets that rotates due to nine electric coils evenly spaced around the rotor. The principle behind levitation of the rotor and the dynamic forces on it are described in detail. An optical encoder feedback system is designed and fabricated that controls the frequency of the levitating rotor. The current input to the coils is given through a driving circuit that amplifies a DC pulse signal generated by a control algorithm designed in LabVIEW. The driving circuit allows current to flow through one phase at a time, which produces a magnetic field strong enough to spin the rotor. Experiments suggest that the optical encoder feedback control system can do reference tracking on the levitating rotor. The designed control algorithm can drive the rotor to specified reference frequencies up to 1.3Hz using the optical encoder measurements. © Taylor & Francis Group, LLC.